THU0434 KNEE JOINT DISTRACTION AS STANDARD OF CARE TREATMENT FOR KNEE OSTEOARTHRITIS: A COMPARISON WITH CLINICAL TRIAL PATIENTS. (June 2019) - Jansen, Mylène; Mastbergen, Simon; Empelen, Michelle Van; Kester, Esmee; Lafeber, Floris; Custers, Roel
Abstract : Background: Knee joint distraction (KJD) has been evaluated as joint-preserving treatment for patients with knee osteoarthritis (OA) in 3 clinical trials since 2004. KJD aims to delay a total knee arthroplasty (TKA) in young knee OA patients, to decrease the risk for revision surgery. KJD temporarily separates the tibia and femur, unloading the knee joint. In an open prospective study (OPS) and 2 randomized controlled trials (RCTs), KJD showed cartilage regeneration and clinical improvement 1, 2 . Since 2014, KJD is a standard of care treatment option in several Dutch hospitals for younger (≤65 yrs) knee OA patients. Objectives: Compare baseline characteristics and clinical outcome at 1 year post-treatment between KJD patients treated in regular care vs study conditions. Methods: In the OPS, patients (n=20; age <60 years) with end-stage OA indicated for TKA were treated with KJD for 8 weeks between 2004 and 2006. In an RCT comparing KJD with TKA, end-stage knee OA patients considered for TKA were treated with KJD (n=19; age <65 years) and completed 1-year follow-up. In an RCT comparing KJD with HTO, medial knee OA patients considered for HTO were treated with KJD (n=22; age <65 years). In both RCTs, patients were treated with KJD for 6 weeks between 2011 and 2014. From 2014-2017, 84 patients were treated with 6-week KJD in regular care and available for 1-year follow-up. All distraction surgery was performed using two external fixators with built-in springs. The knee was distracted 5 mm and weight-bearing was supported. WOMAC questionnaires were assessed at baseline (0) and 12 months. Only regular care patients who completed both questionnaires were included in analyses. Baseline patient characteristics were compared between 'study' (OPS/RCT) and 'regular care' patients. For each group, the total WOMAC scores and subscales at follow-up were compared to baseline. The influence of different characteristics on the 1-year change in WOMAC scores was analyzed. Characteristics predicting being a responder to KJD treatment were analyzed according to the OMERACT-OARSI responder criteria, defined as an increase of ≥50% and ≥20 points in WOMAC pain or function scales, or a ≥20% and ≥10-point improvement in both scales. Results: In regular care, 41 patients completed both questionnaires. Baseline characteristics for both groups are shown in table I, showing a significant, but small difference in distraction duration, which was longer for study patients, but shorter when excluding the OPS patients who received distraction 2 weeks longer. The total WOMAC score and subscales for both groups increased significantly at 1 year compared to baseline (figure 1 ). The increase in total WOMAC and all subscales was over 15 points and thus clinically significant for both groups. The increase in the WOMAC function subscale was statistically, but not clinically, significantly higher for study patients (6.7 points) than regular care patients, while the total WOMAC, pain and stiffness were not different between groups (figure 1 ). After 1 year, 69% of patients were responders (60% regular care, 75% study patients, p=0.120). None of the baseline characteristics could significantly predict being a responder or had a significant influence on the increase in total WOMAC. Conclusion: KJD results in a statistically and clinically significant 1-year improvement in total WOMAC and subscales for most patients. There were no clinically relevant differences between study and regular care patients. Longer follow-up will show whether this is maintained. As such, KJD not only shows good efficacy in study conditions, but also in regular care and can be a joint-preserving treatment of choice for young knee OA patients. References: [1] Van der Woude et al, Cartilage 2017;8(3):263-271. [2] Jansen et al, Cartilage (accepted) Disclosure of Interests: Mylène Jansen: None declared, Simon Mastbergen Grant/research support from: FOREUM; Dutch Arthritis Society, Michelle Van Empelen: None declared, Esmee Kester: None declared, Floris Lafeber Shareholder of: ArthroSave, Grant/research support from: FOREUM; Dutch Arthritis Society, Roel Custers: None declared